(untitled) (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: This prospective study, conducted with patients from the multidisciplinary post-COVID outpatient clinic at the Pulmonary Division of the Cantonal Hospital Winterthur, aimed to investigate changes in patients’ main symptoms, elements that aided in coping with the condition and satisfaction with the consulting and therapeutic interventions. METHODS: After obtaining ethical approval, fifty patients were consecutively included in this longitudinal study, which incorporated three survey times post-consultation: t1 (0–7 days), t2 (4–8 weeks) and t3 (4–6 months). The survey comprised standardised questionnaires, including the Hospital Anxiety and Depression Scale, the Post-COVID-19 Functional Status scale and the Chalder Fatigue scale, along with study-specific questions regarding symptoms and reasons for consulting the post-COVID outpatient clinic. Additionally, ten patients were invited to participate in qualitative individual interviews at t2 and t3. RESULTS: The study was conducted between November 2021 and February 2023. The median age of the 50 participants was 47 years (IQR: 36–55), with 66% (33/50) being female. Most participants (66% or 33/50) reported no pre-existing conditions prior to COVID-19 infection, and only six patients required hospitalisation during the acute phase of their infection. Visits to the multidisciplinary post-COVID clinic occurred approximately eight months post-infection, with referrals primarily made by primary care physicians (82% or 41/50). The majority of patients experienced persistent tiredness, exhaustion and fatigue (94% or 47/50), along with reduced physical performance (82% or 41/50), while pain or breathing difficulties were less frequently mentioned. At t1, around half of the patients were fully or partially unable to work, a proportion that reduced to around a third by t3. Symptoms generally decreased over time, with significant improvements observed between t2 and t3. However, subjectively perceived cognitive limitations worsened or were reported more frequently over time. Most patients (96% or 48/50) felt well cared for throughout their consultations. In qualitative interviews, patients highlighted the medical staff’s attentiveness and the time dedicated to consultations, which made them feel that their complaints were taken seriously and that they received appropriate information. CONCLUSIONS: The results confirmed that the multidisciplinary post-COVID outpatient clinic met most respondents’ expectations. Patients found that the attentive interprofessional coaching was most helpful in coping with their illness. However, participants also noted long waiting times and expressed a desire for earlier admission to the clinic.